You are on page 1of 23

Equations Reducible to Quadratic Equations

Exercise 4.2
Solve the following equations:
1. x 4 6 x 2 + 8 = 0
Solution:
x4 6 x2 + 8 = 0
Let y = x 2 and y 2 = x 4
The above equation becomes: y 2 6 y + 8 = 0
y2 6 y + 8 = 0
y2 4 y 2 y + 8 = 0
y ( y 4) 2( y 4) = 0
( y 2)( y 4) = 0
y 2 = 0 and y 4 = 0
y=2
y=4
2
As, y = x
x2 = 2
x2 = 4
x = 2
x= 2
solution set = { 2, 2, 2, 2}
2. x 2 10 = 3 x1
Solution:
x 2 10 = 3 x 1
x 2 3 x 1 10 = 0
Let y = x 1 and y 2 = x 2
The above equation becomes: y 2 3 y 10 = 0
y 2 5 y + 2 y 10 = 0
y ( y 5) + 2( y 5) = 0
( y + 2)( y 5) = 0
y = 2
y =5
1
As, y = x
x 1 = 2
x 1 = 5
( x 1 )1 = ( 2)1
( x 1 ) 1 = (5)1
1
1
x=
x=
2
5
1 1
solution set = { , }
2 5

Mathematics Notes for FSc Part-I

Prepared by Bilal

3. x 6 9 x3 + 8 = 0
Solution:
x 6 9 x3 + 8 = 0
Let y = x 3 and y 2 = x6
The above equation becomes: y 2 9 y + 8 = 0
y2 8 y y + 8 = 0
y ( y 8) 1( y 8) = 0
( y 1)( y 8) = 0
y =1
y =8
3
As, y = x
x3 = 1
x3 = 8
First take: x 3 = 1
x3 1 = 0
( x 1)( x 2 + x + 1) = 0
x 1 = 0
x2 + x + 1 = 0
1 1 4
x =1
by using quadratic formula
x=
2
1 3
x=
2
1 3i
x=
2
3
Now take: x 8 = 0
( x)3 (2)3 = 0
( x 2)( x 2 + 2 x + 4) = 0
x2= 0
x2 + 2x + 4 = 0
2 4 16
x=2
x=
2
2 12
x=
2
2 2 3
x=
2
2(1 3)
x=
2
x = 1 3
Hence, solution set = {1, 2,

1 3i
, 1 3}
2

Mathematics Notes for FSc Part-I

Prepared by Bilal

4. 8 x 6 19 x3 27 = 0
Solution:
Let y = x 3 and y 2 = x6
The above equation becomes: 8 y 2 19 y 27 = 0
Use quadratic formula,
Here, a = 8 , b = 19 and c = 27
y=

(19) (19) 2 4(8)(27)


2(8)

19 1225
16
19 35
y=
16
19 + 35
y=
16
54
y=
16
27
y=
8
As, y = x3
27
x3 =
8
y=

3
First take: x =

19 35
16
16
y=
16
y=

y = 1

x 3 = 1
27
8

27
=0
8
3
( x)3 ( )3 = 0
2
3 2 3x 9
( x )( x + + ) = 0
2
2 4
3
3x 9
x =0
x2 + + = 0
2
2 4
3
3
9
3
( ) 2 4(1)( )
x=
2
4
x= 2
2
2(1)
x3

3
9

9
4
x= 2
2
3
27

4
x= 2
2
Mathematics Notes for FSc Part-I

Prepared by Bilal

3
(9)(3)

4
x= 2
2
3 3
i
x= 2 2
2
3 3

3
x= 2 2
2
3
(1 3i )
x= 2
2
3(1 3i )
x=
4

Now take: y = 1
x 3 = 1
x3 + 1 = 0
( x + 1)( x 2 + x + 1) = 0
x +1 = 0
x2 + x + 1 = 0
1 1 4
x = 1
by using quadratic formula
x=
2
1 3
x=
2
1 3i
x=
2
3 1 3i 3(1 3i )
Hence, solution set = {1, ,
,
}
2
2
4
2

5. x 5 + 8 = 6 x 5
Solution:
2

x 5 + 8 = 6x5
1

Let y = x 5 and y 2 = x 5
The above equation becomes:
y2 + 8 = 6 y
y2 6 y + 8 = 0
y2 4 y 2 y + 8 = 0
y ( y 4) 2( y 4) = 0
( y 2)( y 4) = 0

Mathematics Notes for FSc Part-I

Prepared by Bilal

y2 =0
y=2

y4 =0
y=4
1

As, y = x 5
1

x5 = 2

x5 = 4

( x 5 )5 = (2)5
( x 5 )5 = (4)5
x = 32
x = 1024
solution set = {32,1024}
6. ( x + 1)( x + 2)( x + 3)( x + 4) = 24
Solution:
( x + 1)( x + 2)( x + 3)( x + 4) = 24
( x + 1)( x + 4)( x + 2)( x + 3) = 24
( x 2 + 4 x + x + 4)( x2 + 3 x + 2 x + 6) = 24
( x 2 + 5 x + 4)( x2 + 5 x + 6) = 24
Let y = x 2 + 5 x
The above equation becomes:
( y + 4)( y + 6) = 24
y 2 + 6 y + 4 y + 24 = 24
y 2 + 10 y = 0
y ( y + 10) = 0
y=0
As, y = x 2 + 5 x
x2 + 5x = 0

y + 10 = 0
x 2 + 5 x + 10 = 0
5 25 4(1)(10)
x=
Using Quadratic formula
2(1)

x( x + 5) = 0

5 15
2
5 15i
x = 5
x=
2
5 15i
Hence, solution set = {0, 5,
}
2
x=0

x+5 = 0

x=

7. ( x 1)( x + 5)( x + 8)( x + 2) 880 = 0


Solution:
( x 1)( x + 5)( x + 8)( x + 2) 880 = 0
( x 1)( x + 8)( x + 2)( x + 5) 880 = 0
( x 2 + 8 x x 8)( x2 + 5 x + 2 x + 10) 880 = 0
Mathematics Notes for FSc Part-I

Prepared by Bilal

( x 2 + 7 x 8)( x 2 + 7 x + 10) 880 = 0


Let y = x 2 + 7 x
The above equation becomes:
( y 8)( y + 10) 880 = 0
y 2 + 10 y 8 y 80 880 = 0
y 2 + 2 y 960 = 0
2 4 4(1)(960)
by using Quadratic formula
2
2 3844
y=
2
2 62
y=
2
2 + 62
2 62
y=
y=
2
2
y = 30
y = 32
As, y = x 2 + 7 x
x 2 + 7 x = 30
x 2 + 7 x = 32
x 2 + 7 x 30 = 0
x 2 + 7 x + 32 = 0
7 49 4(1)(32)
x 2 + 10 x 3x 30 = 0
x=
2
7 79
x( x + 10) 3( x + 10) = 0
x=
2
7 79i
( x 3)( x + 10) = 0
x=
2
x 3 = 0
x + 10 = 0
x=3
x = 10
7 79i
Hence, solution set = {10,3,
}
2
y=

8. ( x 5)( x 7)( x + 6)( x + 4) 504 = 0


Solution:
( x 5)( x 7)( x + 6)( x + 4) 504 = 0
( x 5)( x + 4)( x + 6)( x 7) 504 = 0
( x 2 + 4 x 5 x 20)( x2 7 x + 6 x 42) 504 = 0
( x 2 x 20)( x2 x 42) 504 = 0
Let y = x 2 x
The above equation becomes:
( y 20)( y 42) 504 = 0
y 2 42 y 20 y + 840 504 = 0
Mathematics Notes for FSc Part-I

Prepared by Bilal

y 2 62 y + 336 = 0
y=

(62) (62) 2 4(1)(336)


2(1)

62 2500
2
62 50
y=
2
62 + 50
62 50
y=
y=
2
2
y = 56
y=6
2
As, y = x x
x 2 x = 56
x2 x = 6
x 2 x 56 = 0
x2 x 6 = 0
x 2 8 x + 7 x 56 = 0
x 2 3x + 2 x 6 = 0
x( x 8) + 7( x 8) = 0
x( x 3) + 2( x 3) = 0
( x + 7)( x 8) = 0
( x + 2)( x 3) = 0
x+7 =0
x 8 = 0
x+2=0
x 3 = 0
x = 7
x =8
x = 2
x=3
{

2,3,

7,8}
Hence, solution set =
y=

9. ( x 1)( x 2)( x 8)( x + 5) + 360 = 0


Solution:
( x 1)( x 2)( x 8)( x + 5) + 360 = 0
( x 2 2 x x + 2)( x2 + 5 x 8 x 40) + 360 = 0
( x 2 3 x + 2)( x 2 3 x 40) + 360 = 0
Let y = x 2 3x
The above equation becomes:
( y + 2)( y 40) + 360 = 0
( y 2 40 y + 2 y 80) + 360 = 0
y 2 38 y + 280 = 0
y 2 28 y 10 y + 280 = 0
y ( y 28) 10( y 28) = 0
( y 10)( y 28) = 0
y 10 = 0
As, y = x 2 3x
x 2 3 x 10 = 0
x 2 5 x + 2 x 10 = 0
x( x 5) + 2( x 5) = 0
( x + 2)( x 5) = 0
Mathematics Notes for FSc Part-I

y 28 = 0
x 2 3 x 28 = 0
x 2 7 x + 4 x 28 = 0
x( x 7) + 4( x 7) = 0
( x + 4)( x 7) = 0

Prepared by Bilal

x+2=0
x 5 = 0
x = 2
x=5
Hence, solution set = {2,5, 4, 7}

x+4=0
x = 4

x7 = 0
x=7

10. ( x + 1)(2 x + 3)(2 x + 5)( x + 3) = 945


Solution:
( x + 1)(2 x + 3)(2 x + 5)( x + 3) = 945
( x + 1)( x + 3)(2 x + 3)(2 x + 5) = 945
( x 2 + 3 x + x + 3)(4 x2 + 10 x + 6 x + 15) = 945
( x 2 + 4 x + 3)(4 x2 + 16 x + 15) = 945
( x 2 + 4 x + 3)(4( x2 + 4 x) + 15) = 945
Let y = x 2 + 4 x
The above equation becomes:
( y + 3)(4 y + 15) = 945
4 y 2 + 15 y + 12 y + 45 945 = 0
4 y 2 + 27 y 900 = 0
27 (27) 2 4(4)(900)
by using quadratic formula
y=
2(4)
27 729 + 14400
8
27 15129
y=
8
27 123
y=
8
27 + 123
y=
8
y=

y = 12

27 123
8
75
y=
4
y=

As, y = x 2 + 4 x
x 2 + 4 x = 12
x 2 + 4 x 12 = 0
x + 6 x 2 x 12 = 0
2

x( x + 6) 2( x + 6) = 0

Mathematics Notes for FSc Part-I

75
4
75
x2 + 4x +
=0
4
x2 + 4x =

x=

4 16 4(1)(

75
)
4

2
4 16 75
x=
2

Prepared by Bilal

4 59
2
4 59i
x=
2

( x 2)( x + 6) = 0
x2= 0

x+6= 0

x=2

x = 6

Hence, solution set = {6, 2,

x=

4 59i
}
2

11. (2 x 7)( x 2 9)(2 x + 5) 91 = 0


Solution:
(2 x 7)( x 2 9)(2 x + 5) 91 = 0
(2 x 7)( x 3)( x + 3)(2 x + 5) 91 = 0
(2 x 7)( x + 3)( x 3)(2 x + 5) 91 = 0
(2 x 2 + 6 x 7 x 21)(2 x2 + 5 x 6 x 15) 91 = 0
(2 x 2 x 21)(2 x2 x 15) 91 = 0
Let y = 2 x 2 x
The above equation becomes:
( y 21)( y 15) 91 = 0
( y 2 15 y 21 y + 315) 91 = 0
y 2 36 y + 224 = 0
y 2 28 y 8 y + 224 = 0
y ( y 28) 8( y 28) = 0
( y 8)( y 28) = 0
y 8 = 0
y 28 = 0
2
As, y = 2 x x
2 x2 x 8 = 0
2 x 2 x 28 = 0
Using Quadratic formula:
2 x 2 8 x + 7 x 28 = 0
(1) 1 4(2)(8)
2 x( x 4) + 7( x 4) = 0
x=
2(2)
x=

1 65
4

(2 x + 7)( x 4) = 0
2x + 7 = 0
7
x=
2

x4= 0
x=4

7 1 65
Hence, solution set = {4, ,
}
2
4

Mathematics Notes for FSc Part-I

Prepared by Bilal

12. ( x 2 + 6 x + 8)( x 2 + 14 x + 48) = 105


Solution:
( x 2 + 6 x + 8)( x 2 + 14 x + 48) = 105
( x 2 + 4 x + 2 x + 8)( x2 + 8 x + 6 x + 48) = 105
x( x + 4) + 2( x + 4)( x( x + 8) + 6( x + 8)) = 105
( x + 2)( x + 4)( x + 6)( x + 8) = 105
Rearranging we have,
( x + 2)( x + 8)( x + 4)( x + 6) = 105
( x 2 + 8 x + 2 x + 16)( x2 + 6 x + 4 x + 24) = 105
( x 2 + 10 x + 16)( x2 + 10 x + 24) = 105
Let y = x 2 + 10 x
The above equation becomes:
( y + 16)( y + 24) = 105
y 2 + 24 y + 16 y + 384 105 = 0
y 2 + 40 y + 279 = 0
y=

40 (40) 2 4(1)(279)
2(1)

40 1600 1116
2
40 484
y=
2
40 22
y=
2
40 + 22
y=
2
y = 9
As, y = x 2 + 10 x
x 2 + 10 x = 9
x 2 + 10 x + 9 = 0
y=

x2 + 9 x + x + 9 = 0
x( x + 9) + 1( x + 9) = 0
( x + 1)( x + 9) = 0
x +1 = 0

x+9 = 0

Mathematics Notes for FSc Part-I

40 22
2
y = 31
y=

x 2 + 10 x = 31
x 2 + 10 x + 31 = 0
10 100 4(1)(31)
x=
2
10 100 124
x=
2
10 24
x=
2
10 24i
x=
2

Prepared by Bilal

10 2 6i
2
2(5 6i )
x=
2
x = 5 6i
Hence, solution set = {1, 9 5 6i}
x = 1

x = 9

x=

13. ( x 2 + 6 x 27)( x2 2 x 35) = 385


Solution:
( x 2 + 6 x 27)( x2 2 x 35) = 385
( x 2 + 9 x 3 x 27)( x2 7 x + 5 x 35) = 385
( x( x + 9) 3( x + 9))( x( x 7) + 5( x 7)) = 385
( x 3)( x + 9)( x + 5)( x 7) = 385
Rearranging we have,
( x 3)( x + 5)( x + 9)( x 7) = 385
( x 2 + 5 x 3 x 15)( x2 7 x + 9 x 63) = 385
( x 2 + 2 x 15)( x2 + 2 x 63) = 385
Let y = x 2 + 2 x
The above equation becomes:
( y 15)( y 63) = 385
y 2 63 y 15 y + 945 = 385
y 2 78 y + 945 385 = 0
y 2 78 y + 560 = 0
y=

(78) (78) 2 4(1)(560)


by using quadratic formula
2(1)

78 6084 2240
2
78 3844
y=
2
78 62
y=
2
78 + 62
y=
2
y = 70
As, y = x 2 + 2 x
x 2 + 2 x = 70
x 2 + 2 x 70 = 0
y=

Mathematics Notes for FSc Part-I

78 62
2
y =8
y=

x2 + 2x = 8
x2 + 2x 8 = 0

Prepared by Bilal

x=

2 4 4(1)(70)
2(1)

x2 + 4x 2x 8 = 0

2 4 71
x( x + 4) 2( x + 4) = 0
2
2 2 71
( x 2)( x + 4) = 0
x=
2
2(1 71)
x2= 0
x+4=0
x=
2
x=2
x = 4
x = 1 71
Hence, solution set = {4, 2, 1 71}
x=

14. 4.22 x +1 9.2x + 1 = 0


Solution:
4.22 x +1 9.2x + 1 = 0
4.22 x.21 9.2x + 1 = 0
8.22 x 9.2 x + 1 = 0
( y ) 2 = (2 x )2 y 2 = 22 x
Let y = 2 x
The above equation becomes:
8 y2 9 y +1 = 0
8 y2 8 y y +1 = 0
8 y ( y 1) 1( y 1) = 0
(8 y 1)( y 1) = 0
8 y 1 = 0
y 1 = 0
1
y=
8
As, y = 2 x
1
2x =
8
1
2 x = ( )3
2
1
2 x = (2) 3 ( ) = a 1
a
x = 3
Hence, solution set = {3, 0}

y =1

2x = 1
2 x = (2)0

a0 = 1

x=0

15. 2 x + 2 x + 6 20 = 0
Solution:
2 x + 2 x + 6 20 = 0
2 x + 2 x.26 20 = 0
Mathematics Notes for FSc Part-I

Prepared by Bilal

1 6
.2 20 = 0
2x
Let y = 2 x
The above equation becomes:
1
y + 64 20 = 0
y
2
y + 64
= 20
y
2x +

y 2 + 64 = 20 y
y 2 20 y + 64 = 0
y 2 16 y 4 y + 64 = 0
y ( y 16) 4( y 16) = 0
( y 4)( y 16) = 0
y4 =0
y 16 = 0
x
As, y = 2
2x 4 = 0
2 x 16 = 0
2 x = 16
2x = 4
2 x = 22
2 x = 24
x=2
x=4
Hence, solution set = {2, 4}

a b = a c b = c Hence, 2 x = 22 x = 2 , and
2 x = 24 x = 4

16. 4 x 3.2 x+3 + 128 = 0


Solution:
4 x 3.2 x+3 + 128 = 0
4 x 3.2 x.23 + 128 = 0
4 x 24.2x + 128 = 0
(22 ) x 24.2 x + 128 = 0
(a m )n = a mn
22 x 24.2 x + 128 = 0
( y ) 2 = (2 x )2 y 2 = 22 x
Let y = 2 x
The above equation becomes:
y 2 24 y + 128 = 0
y 2 16 y 8 y + 128 = 0
y ( y 16) 8( y 16) = 0
( y 8)( y 16) = 0
y 8 = 0
y 16 = 0
y =8
y = 16
x
As, y = 2

Mathematics Notes for FSc Part-I

Prepared by Bilal

2x = 8
2 x = 16
2 x = 23
2 x = 24
x=3
x=4
Hence, solution set = {3, 4}
17. 32 x 1 12.3x + 81 = 0
Solution:
32 x 1 12.3x + 81 = 0
32 x.31 12.3x + 81 = 0
32 x
12.3x + 81 = 0
3
y 2 = 32 x
Let y = 3x
The above equation becomes:
y2
12 y + 81 = 0
3
y 2 36 y
= 81
3
y 2 36 y = 243
y 2 36 y + 243 = 0
y=

(36) (36) 2 4(1)(243)


by using quadratic formula
2(1)

36 1296 972
2
36 324
y=
2
36 18
y=
2
36 + 18
36 18
y=
y=
2
2
y = 27
y =9
As, y = 3x
3x = 27
3x = 9
3x = 33
3x = 32
x=3
x=2
{2,3}
Hence, solution set =
y=

Mathematics Notes for FSc Part-I

Prepared by Bilal

1 2
1
18. ( x + ) 3( x + ) 4 = 0
x
x
Solution:
1
1
( x + ) 2 3( x + ) 4 = 0
x
x
1
Let y = x +
x
The above equation becomes:
y2 3y 4 = 0
y2 4 y + y 4 = 0
y ( y 4) + 1( y 4) = 0
( y + 1)( y 4) = 0
y +1 = 0
y = 1
1
As, y = x +
x
1
x + = 1
x
2
x +1
= 1
x
x2 + 1 = x
x2 + x + 1 = 0
1 1 4
x=
2
1 3
x=
2
1 3i
x=
2

Hence, solution set = {

y4 =0
y=4

1
=4
x
x2 + 1
=4
x
x2 + 1 = 4 x
x2 4x + 1 = 0
(4) 16 4
by using quadratic formula
x=
2
4 12
x=
2
4 43
x=
2
42 3
x=
2
2(2 3)
x=
2
x = 2 3
x+

1 3i
, 2 3}
2

Mathematics Notes for FSc Part-I

Prepared by Bilal

2
19. x + x 4 +

1 1
+
=0
x x2

Solution:
1 1
+
=0
x x2
Rearranging we have,
1
1
x + + x2 + 2 4 = 0
x
x
x2 + x 4 +

1 2
1
2
Add 2 to both the sides for completing the square, ( x + ) = x + 2 + 2
x
x
1
1
x + + x2 + 2 + 2 4 = 2
x
x
1
1 2
x + + (x + ) = 6
x
x
1
Let y = x +
x
The above equation becomes:
y + y2 6 = 0
y2 + 3y 2 y 6 = 0
y ( y + 3) 2( y + 3) = 0
( y 2)( y + 3) = 0
y2 =0
y=2
1
As, y = x +
x
1
x+ =2
x
2
x +1
=2
x
x2 2x + 1 = 0
2 44
x=
2
2 0
x=
2
x =1
Hence, solution set = {1,

y+3= 0
y = 3

1
= 3
x
x2 + 1
= 3
x
x 2 + 3x + 1 = 0
3 9 4
x=
2
3 5
x=
2
x+

3 5
}
2

Mathematics Notes for FSc Part-I

Prepared by Bilal

1 2
1
20. ( x ) + 3( x + ) = 0
x
x
Solution:
1
1
( x ) 2 + 3( x + ) = 0
x
x
1
1
x 2 2 + 2 + 3( x + ) = 0
x
x
1
1
x 2 2 + 2 + 2 + 3( x + ) = 2 Add 2 to both sides for completing the square
x
x
1
1
x 2 + 2 + 2 + 3( x + ) = 2 + 2
x
x
1
1
( x + ) 2 + 3( x + ) 4 = 0
x
x
1
Let y = x +
x
The above equation becomes:
y2 + 3y 4 = 0
y2 + 4 y y 4 = 0
y ( y + 4) 1( y + 4) = 0
( y 1)( y + 4) = 0
y 1 = 0
y =1
1
As, y = x +
x
1
x + =1
x
2
x +1
=1
x
x2 + 1 = x
x2 x + 1 = 0
(1) 1 4
x=
2
1 3
x=
2
1 3i
x=
2

Mathematics Notes for FSc Part-I

y+4=0
y = 4

1
= 4
x
x2 + 1
= 4
x
x 2 + 1 = 4 x
x2 + 4x + 1 = 0
(4) 16 4
x=
2
4 12
x=
2
4 4 3
x=
2
4 2 3
x=
2
x+

Prepared by Bilal

2(2 3)
2
x = 2 3
x=
1 3i
Hence, solution set = {
, 2 3}
2
21. 2 x 4 3 x3 x2 3x + 2 = 0
Solution:
2 x 4 3 x3 x2 3x + 2 = 0 divide both sides by x 2
3 2
2 x 2 3x 1 + 2 = 0
x x
1
1
2( x 2 + 2 ) 3( x + ) = 1 add 4 both sides for completing the square
x
x
1
1
2( x 2 + 2 ) 3( x + ) + 4 = 1 + 4
x
x
1
1
2( x 2 + 2 + 2 ) 3( x + ) = 1 + 4 the 4 becomes 2 inside the parenthesis,
x
x
because it is multiplying by 2.
1 2
1
2( x + ) 3( x + ) = 5
x
x
1
Let y = x +
x
The above equation becomes:
2 y2 3y 5 = 0
2 y2 5 y + 2 y 5 = 0
y (2 y 5) + 1(2 y 5) = 0
( y + 1)(2 y 5) = 0
y +1 = 0
2y 5 = 0
y = 1
2y = 5
5
y=
2
1
As, y = x +
x
1
1 5
x + = 1
x+ =
x
x 2
2
2
x +1
x +1 5
= 1
=
x
x
2
5x
x2 + 1 =
x2 + x + 1 = 0
2

Mathematics Notes for FSc Part-I

Prepared by Bilal

1 1 4
2
1 3
x=
2
1 3i
x=
2
x=

5x
= 1
2
2 x2 5x
= 1
2

x2

2 x 2 5 x = 2

2 x2 5x + 2 = 0
2 x2 4x x + 2 = 0
2 x( x 2) 1( x 2) = 0
(2 x 1)( x 2) = 0
2x 1 = 0
x2=0
1
x=
x=2
2
1
1 3i
Hence, solution set = { , 2,
}
2
2
22. 2 x 4 + 3 x3 4 x2 3 x + 2 = 0
Solution:
2 x 4 + 3 x3 4 x2 3 x + 2 = 0 divide both sides by x 2
3 2
2 x 2 + 3x 4 + 2 = 0
x x
1
1
2( x 2 + 2 ) + 3( x ) = 4
x
x
1
1
2( x 2 2 + 2 ) + 3( x ) = 4 4
x
x
1
1
2( x ) 2 + 3( x ) = 0
x
x
1
Let y = x
x
The above equation becomes:
2 y2 + 3y = 0
y (2 y + 3) = 0
y=0
2y + 3 = 0
3
y=
2
1
As, y = x
x
1
1
3
x =0
x =
x
x
2

Mathematics Notes for FSc Part-I

Prepared by Bilal

x2 1
=0
x
x2 1 = 0
x2 = 1
x = 1

x2 1
3
=
x
2
3x
x2 1 =
2
3
x
x2 +
=1
2
2 x 2 + 3x
=1
2
2 x 2 + 3x = 2
2 x 2 + 3x 2 = 0

2 x2 + 4x x 2 = 0
2 x( x + 2) 1( x + 2) = 0
(2 x 1)( x + 2) = 0
2x 1 = 0
x+2=0
1
x=
x = 2
2
1
Hence, solution set = {1, 2, ,}
2
23. 6 x 4 35 x3 + 62 x2 35 x + 6 = 0
Solution:
6 x 4 35 x3 + 62 x2 35 x + 6 = 0 divide both sides by x 2
35 6
6 x 2 35 x + 62 + 2 = 0
x x
1
1
6( x 2 + 2 ) 35( x + ) = 62
Add 12 to both sides for completing the square.
x
x
1
1
6( x 2 + 2 + 2 ) 35( x + ) = 62 + 12
(12 becomes 2 inside brackets, because brackets
x
x
are multiplying by 6.)
1 2
1
6( x + ) 35( x + ) = 50
x
x
1
Let y = x +
x
The above equation becomes:
6 y 2 35 y + 50 = 0
(35) (35) 2 4(6)(50)
y=
2(6)
y=

35 1225 1200
12

Mathematics Notes for FSc Part-I

Prepared by Bilal

35 25
12
35 5
y=
12
35 + 5
y=
12
10
y=
3
1
As, y = x +
x
1 10
x+ =
x 3
2
x + 1 10
=
x
3
10 x
x2 + 1 =
3
10 x
x2
= 1
3
3x 2 10 x
= 1
3
3 x 2 10 x = 3
3 x 2 10 x + 3 = 0

1 5
=
x 2
x2 + 1 5
=
x
2
5x
x2 + 1 =
2
5x
x2
= 1
2
2 x2 5x
= 1
2
2 x 2 5 x = 2
2 x2 5x + 2 = 0

(10) (10) 2 4(3)(3)


x=
2(3)

(5) (5) 2 4(2)(2)


x=
2(2)

y=

10 100 36
6
10 64
x=
6
10 8
x=
6
10 + 8
10 8
x=
x=
6
6
1
x=
x=3
3
x=

35 5
12
5
y=
2
y=

x+

5 25 16
4
5 9
x=
4
53
x=
4
5+3
53
x=
x=
4
4
1
x=
x=2
2
x=

1 1
Hence, solution set = {2, ,3, }
2 3

Mathematics Notes for FSc Part-I

Prepared by Bilal

4
2
24. x 6 x + 10

6 1
+
=0
x2 x4

Solution:
6 1
+
=0
x2 x4
1
1
x 4 + 4 6( x2 + 2 ) = 10
x
x
1
1
x 4 + 2 + 4 6( x2 + 2 ) = 10 + 2
x
x
1
1
( x 2 + 2 )2 6( x2 + 2 ) = 8
x
x
1
2
Let y = x + 2
x
The above equation becomes:
y2 6 y + 8 = 0
x 4 6 x 2 + 10

y2 4 y 2 y + 8 = 0
y ( y 4) 2( y 4) = 0
( y 2)( y 4) = 0
y2 =0
y4 =0
y=2
y=4
1
2
As, y = x + 2
x
1
1
x2 + 2 = 2
x2 + 2 = 4
x
x
1
2
First take: x + 2 = 2
x
Add 2 to both sides for completing the square
1
x2 + 2 + 2 = 2 + 2
x
1
( x 2 + 2 )2 = 4
x
1
x 2 + 2 = 2
x
1
1
x2 + 2 = 2
x 2 + 2 = 2
x
x
4
4
x +1
x +1
=2
= 2
2
x
x2
x 4 + 1 = 2 x2
x 4 + 1 = 2 x 2
x4 2 x2 + 1 = 0
x 4 + 2 x2 + 1 = 0
( x 2 1)2 = 0
( x 2 + 1)2 = 0

Mathematics Notes for FSc Part-I

Prepared by Bilal

x2 1 = 0
x2 = 1
x = 1
2
Now take: x +

x2 + 1 = 0
x 2 = 1
x = i
1
=4
x2

x4 + 1
=4
x2
x 4 + 1 = 4 x2
x4 4 x2 + 1 = 0
Let u = x 2
The above equation becomes:
u 2 4u + 1 = 0
u=

(4) (4) 2 4(1)(1)


2(1)

4 12
2
4 43
u=
2
42 3
u=
2
u = 2 3
As, u = x 2
x2 = 2 3
u=

x = 2 3
Hence, solution set = {1, i, 2 3}

Mathematics Notes for FSc Part-I

Prepared by Bilal